Tinjauan Hukum Islam terhadap Praktik Perjanjian Utang Piutang Dibayar Jasa Kerja Di Desa Seburing Kecamatan Semparuk Kabupaten Sambas - Hairoman (Lunggi Journal, 2024)
The aim of this research is to reveal about 1) Knowing the practice of debts and receivables being paid for work services in Seburing Village, Semparuk District, Sambas Regency, 2) Knowing the Islamic law review of the practice of debts and receivables being paid for work services in Seburing Village, Semparuk District, Sambas Regency. This research uses descriptive research with a qualitative approach. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this research show that: 1) The practice of paying debts and receivables agreements for work services in Seburing Village, Semparuk District, Sambas Regency, is one of the communities that carries debts and receivables in the form of basic kitchen necessities and agricultural products. The perpetrator or business owner provides a loan to the recipient of the debt or the debtor, then enters into an agreement to pay for the goods in the form of work in the amount that will be written on the note. The number of notes that are often owed starts from Rp. 200,000.00 to Rp. 3,000,000.00. The occurrence of debt and receivable agreements in Seburing Village, Semparuk District, because it tends to be based on a sense of trust in giving debts to known consumers and the existence of a well-established relationship, and has become a habit of the local community, 2) Review of Islamic law regarding the practice of debt and receivable agreements paid work services in Seburing Village, Semparuk District, Sambas Regency, permitted by the ulama based on the Al-Qur'an and the hadith of the Prophet SAW and the Ijma' Ulama. Indeed, Allah SWT teaches His servants to lend something for the religion of Allah SWT, in the words of Allah SWT in Q.S. Al-Baqoroh 2: 245. Meaning: and help you in (doing) virtue and piety, and do not help in committing sins and transgressions. And fear Allah, verily Allah is severe in punishment.